Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 3; b = -2√(6;) c = 2


= 3.2 = 6


And either of their sum or difference = b


= -2√6


Thus the two terms are -√6 and -√6


Sum = -√6 -√6 = -2√6


Product = -√6. -√6 = -6 6 = √6. √6




(On using 3 = √3.√3 and √6 = √3 √2)





Equation has repeated roots


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics